Non-invasive in vivo imaging of caspase-1 activation enables rapid and spatiotemporal detection of acute and chronic inflammatory disorders. (January 2020) - Ko, Young Ji; Lee, Jae-Won; Yang, Eun-Jeong; Jang, Nayoon; Park, Jooho; Jeon, Yoon Kyung; Yu, Je-Wook; Cho, Nam-Hyuk; Kim, Hye-Sun; Chan Kwon, Ick
Abstract: Inflammasome plays a critical role in diverse inflammatory disorders, including cancers and Alzheimer's disease. It is induced by various pathogenic insults and activates caspase-1, a hallmark executor of inflammasome. Here, we developed an activatable fluorescence probe for visualization of active caspase-1. This caspase-1 probe is biocompatible, efficiently delivered into cells and tissues, and specifically emits fluorescence upon caspase-1 activation as assessed in in vitro and in vivo models of inflammatory conditions. We demonstrated efficient in vivo imaging of caspase-1 activation in early stages of various inflammatory conditions of mice models, including endotoxin shock, inflammatory bowel disorder, transplanted cancer, and Alzheimer's disease. Notably, the caspase-1 probe enables detection of neuroinflammation in vivo two months earlier than cognitive impairments occur in Alzheimer's disease model. We detected significant fluorescence emitted from inflamed sites, as well as their draining lymph nodes, by macroscopic imaging analysis within 30 min after systemic injection of the probe. This novel synthetic probe could be applied for efficient and rapid detection of caspase-1 activity in a spatiotemporal way by non-invasive imaging.